Translation Strategies of Food-Related Culture Specific Items in Indonesian Subtitle of Netflix Series The Final Table - Muhammad Farkhan; Li Unsyah Naimah; M. Agus Suriadi (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2020)
This study aims to find out strategies used in the translation of food-related culture-specific items in Netflix cooking show, The Final Table of UK and USA episodes, and factors that influence the choice of strategies used in translating these items. The study uses discourse analysis as a research design relying on corpuses or food terminologies in Indonesian subtitle and their original as its primary data. All data were marked bold, rewritten, sorted, and classified in accordance with the identified themes of the culture-specific items. The collected data were qualitatively analyzed using Pedersen’s translation strategy, particularly for culture-specific items. The study found out that there were 51 food-related culture-specific items in the source language (SL) with their translations, and there were five translation strategies employed by the translator in rendering these items, namely retention, specification, direct translation, generalization, and substitution. Retention was the most frequently used strategy as it resembled 35 times in the data. The most common factor identified was the non-existence of the source language foodstuff terms in the target language as it existed 21 times out of 51 data. This study recommends the translators of this Netflix to consider the culture when translating from the SL to the target language (TL).